Lorelei Localization and Ovule Ultrastructure in Arabidopsis Thaliana - (:unkn) unknown (My University, 2019)
Communication between the male and female gametophyte is vital to successful fertilization during sexual reproduction in plants. One of the proteins known to be important for communication between the male and female gametophyte is LORELEI (LRE). Several studies have shown that there are defects in pollen tube guidance and synergid degeneration, however this is the first study that shows that cell wall thickness in the female gametophyte may also be affected. Previous confocal studies have documented that LRE is present both in the filiform apparatus and found in puncta throughout the cytoplasm. This study confirmed this, but our studies suggest that the proportions maybe different; in the TEM sections we examined a majority of the LRE seems to be localizing to the filiform apparatus. This study also reported that three Arabidopsis WT accessions had very similar embryo sac ultrastructure, thus for electron microscopy studies data from all these accessions can be used to add robustness to a study with a low WT sample size.
Keywords: Arabidopsis; electron microscopy; Immunogold; LORELEI; TEM; Ultrastructure